2014
DOI: 10.4103/0971-3026.130697
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral encephalopathy with extrapontine myelinolysis in a case of postpartum hypernatremia

Abstract: Extrapontine myelinolysis, a fairly common metabolic disorder, is associated with neurological complications. Central pontine and extrapontine myelinolysis are commonly recognized with rapid correction of sodium. Myelinolysis, however, has rarely been described with hypernatremia. We report a rare case of post-partum hypernatremic encephalopathy associated with serum sodium levels as high as 200 mEq/l on presentation. Although the serum sodium levels were brought down gradually, subsequent imaging showed progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
2
7
0
1
Order By: Relevance
“…Similar cases of hypernatremia myelinolysis have been reported in literature, which were treated with parenteral fluids and steroids [1,2]. Rapid correction of hyponatremia is a well-known cause of central pontine and extrapontinemyelinolysis.…”
Section: Discussionsupporting
confidence: 63%
“…Similar cases of hypernatremia myelinolysis have been reported in literature, which were treated with parenteral fluids and steroids [1,2]. Rapid correction of hyponatremia is a well-known cause of central pontine and extrapontinemyelinolysis.…”
Section: Discussionsupporting
confidence: 63%
“…6 Naik et al reported elevated serum CK levels in nine out of eleven patients. 2 Elevated cretine kinase level in postpartum hypernatremia is also reported by Bhatia et al 7 and Suri et al 8 All our patients had hypermagnesemia which can be explained by acute kidney injury. All patients had normal calcium levels.…”
supporting
confidence: 81%
“…[1011] It also occurred with gradual correction of hyponatremia as well as in normonatremic and hypernatremic patients. [12131415] Several conditions predisposing patients to its development were also found. These include renal failure patients on dialysis, liver failure, and transplantation, malignancies such as lymphoma, carcinoma, cachexia, sepsis, acute pancreatitis, pellagra, and chronic alcoholism.…”
Section: Discussionmentioning
confidence: 99%